2019
DOI: 10.1111/jocn.14942
|View full text |Cite
|
Sign up to set email alerts
|

Overseas qualified nurses’ communication with other nurses and health professionals: An observational study

Abstract: Aims and objectives To understand the interprofessional and intraprofessional communication patterns of overseas qualified nurses as they coordinate care for patients in Australian hospitals. Background Numerous studies have informed the transitioning experiences of overseas qualified nurses with non‐English‐speaking backgrounds working in English‐speaking workplaces. Only a few observational studies have involved examining the intercultural communication experiences of overseas qualified nurses, and none have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 30 publications
(54 reference statements)
1
26
0
Order By: Relevance
“…The findings also demonstrated that social talk between senior (0.4%) and novice (0.2%) nurses was a conversation category that received relatively little attention. Creating opportunities for social talk can be especially important in cultivating positive group cohesion and interpersonal professional relationships [44,45]. Previous studies have pointed to the value of senior nurses engaging novice nurses during their transition period, to provide relevant professional support and discuss issues novice nurses may encounter [15].…”
Section: Discussionmentioning
confidence: 99%
“…The findings also demonstrated that social talk between senior (0.4%) and novice (0.2%) nurses was a conversation category that received relatively little attention. Creating opportunities for social talk can be especially important in cultivating positive group cohesion and interpersonal professional relationships [44,45]. Previous studies have pointed to the value of senior nurses engaging novice nurses during their transition period, to provide relevant professional support and discuss issues novice nurses may encounter [15].…”
Section: Discussionmentioning
confidence: 99%
“…These results support the research conducted by Yaya Wang et al (2018), which explains nurses' positive perceptions of communication with other care giver professionals (24) . Effective communication between health team members is essential for safe and high-quality patient care (37) .…”
Section: Discussionmentioning
confidence: 99%
“…The language barrier can lead to problems such as receiving different information about the same topic, which can decrease IPC (Skjeggestad et al, 2017). It can affect patient safety if the receiver misinterprets the information, or if the person sharing the information does not clearly convey the message resulting in misconstrued information (Philip et al, 2019; Wittenberg et al, 2015). Volunteers used the challenge of the language barrier as an opportunity and motivation in putting effort into understanding each other.…”
Section: Discussionmentioning
confidence: 99%